2017
DOI: 10.1186/s12871-016-0295-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tramadol on postoperative shivering after sevoflurane and remifentanil anesthesia

Abstract: BackgroundsRemifentanil has been reported to cause post-anesthetic shivering (PAS). Higher doses of remifentanil reportedly induce more intense PAS. Tramadol, a synthetic opioid that acts at multiple sites, is considered to be an effective treatment for PAS, but the evidence for its therapeutic benefit after remifentanil anesthesia is limited. We investigated the effect of tramadol on the incidence of PAS after remifentanil anesthesia.MethodsSixty-three patients who had undergone upper abdominal surgery under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Anesthesia and CPB were performed using procedures standard at the 2 institutions. [25,26] Briefly, anesthesia was induced with midazolam, sufentanil, and a muscle relaxant, which was usually etomidate at the Second Affiliated Hospital. Anesthesia was maintained with a continuous infusion of remifentanil, inhalation of sevoflurane, intermittent muscle relaxant, and sufentanil.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anesthesia and CPB were performed using procedures standard at the 2 institutions. [25,26] Briefly, anesthesia was induced with midazolam, sufentanil, and a muscle relaxant, which was usually etomidate at the Second Affiliated Hospital. Anesthesia was maintained with a continuous infusion of remifentanil, inhalation of sevoflurane, intermittent muscle relaxant, and sufentanil.…”
Section: Methodsmentioning
confidence: 99%
“…After CPB, residual blood was collected in a bag containing sodium citrate, neutralized by protamine, and transfused into the patient as described. [26,27]…”
Section: Methodsmentioning
confidence: 99%
“…Mohta et al also reported that tramadol 2 mg/kg provided an effective combination of anti-PS activity and analgesia without excessive sedation [43]. Nakagawa et al showed that the administration of tramadol (3 mg/kg) at induction of anaesthesia significantly reduced the incidence of PS independently of remifentanil concentration used intraoperatively [44]. Ketamine is a competitive antagonist at the NMDA receptor, suggesting that the antishivering effect of tramadol might be mediated by the NMDA receptor [44].…”
Section: Opioid Receptor Agonistsmentioning
confidence: 99%
“…There have been studies that investigated the performances of ProSeal™ LMA (Intavent Orthofix, Maidenhead, UK) in LC 3,4. However, the performances of i-Gel® and AuraGain have not yet been sufficiently investigated.…”
mentioning
confidence: 99%